Crypto-Assets as Innovative Finance Tools - A. V. Krupochkin (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses problems of finding the place of crypto currency in the system of finance tools and its legal status in Russia and the world. The author identifies potential threats for crypto currency users and ways of legal regulation of crypto currency transactions. Terms used in the field of crypto currency are analyzed, key types of crypto currencies are shown and their characteristics are provided. Present day concepts of regulating crypto currency market in Russia and the world are presented. As the methodological basis of the article the author uses dialectical, formal-legal, systematic, comparative-legal, structural and functional methods. In the research the author comes to the conclusion about the necessity to establish state control over crypto currency legal status regulation and to ban its potential negative impact on economy. Therefore, it is essential to develop a bill, which can solve problems of regulation and control of crypto currency transactions.